(untitled) (AACINI - International Journal of Industrial Engineering, 2022)
The food market is experiencing strong challenges to provide healthy, nutritious, sustainable and consumer-friendly options. One of the postulates of sustainable development is "zero hunger" and under this challenge is that a group of researchers from the Facultad de Ingeniería y Ciencias Agropecuarias (FICA) of the National University of San Luis has been conducting research and development. Another of the postulates in/of the Sustainable Development Goals is "affordable and non-polluting energy", then, under these criteria is that the FICA pilot plant has worked on the production of a healthy menu carried out in a production process with a solar dehydrator oven. The development of this healthy menu not only responds to the concern of finding an alternative for the food system of families with different requirements, but also aims to produce it with raw materials that are not destined for the retail market, thus making a use of it; and also with a sustainable production process. In this work, an analysis of the value chain of the healthy menu of FICA is presented, identifying each of the primary activities and the support activities. In addition, the competitive advantages of the aforementioned value chain are also identified.